2000
DOI: 10.1111/j.1746-1561.2000.tb07278.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Tobacco, and Other Psychoactive Drug Use Among High School Students in Bogota, Colombia

Abstract: This descriptive study identified health behaviors practiced by 10th-grade students enrolled in public schools in Bogotá, Colombia. A modified version of the Youth Risk Behavior Survey assessed the health-related behaviors of 1,730 students. In this paper data for tobacco, alcohol, and psychoactive substances use are discussed. A one-way analysis of variance (ANOVA) was used to determine statistical significance among selected behavioral risk areas and the independent variables that were nominally scaled. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 1 publication
3
8
0
4
Order By: Relevance
“…The prevalence of DCS is between 1.3% and 23.0% depending on gender, grade, ethnicity and religion (4)(5)(6)(7)(8) . Studies on Colombian cigarette smoking among high school students are scarce (9)(10)(11) . One research reported prevalence of daily cigarette smoking of 7.7% among 11 th grade students in Medellín (9) and another found prevalence of 16.0%…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of DCS is between 1.3% and 23.0% depending on gender, grade, ethnicity and religion (4)(5)(6)(7)(8) . Studies on Colombian cigarette smoking among high school students are scarce (9)(10)(11) . One research reported prevalence of daily cigarette smoking of 7.7% among 11 th grade students in Medellín (9) and another found prevalence of 16.0%…”
Section: Introductionmentioning
confidence: 99%
“…These studies used the same questionnaire for substance use epidemiological survey (VESPA), however, this instrument is sufficiently accurate if cigarette consumption occurs everyday during the previous month. Another study documented that 11.0% of 10 th grade students enrolled in public schools in Bogotá had smoked every day in the previous month (11) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…En estudiantes de media vocacional se ha observado que el consumo diario de cigarrillo se asocia en forma significativa con una serie de consecuencias negativas tales como consumo de otras sustancias, por ejemplo, alcohol y marihuana, deserción y fracaso académico, accidentes, violencia, relaciones sexuales de alto riesgo para embarazos no planeados o enfermedades transmisibles sexualmente, y suicidio (11)(12)(13).…”
unclassified